Implementation SQ3R Method To Improve Students’ Comprehension Of Reading English Textbook (E-Book) Of Muhammadiyah University Of Buton - Ratna Said; Agusalim Agusalim (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2020)
This research aimed to determine the improving of students' comprehension in reading English textbook (e-book) through SQ3R at Communication Science Study Program, Muhammadiyah University of Buton. This research was classroom action research. Respondence of this research are 28 students in class B odd semester of 2018/2019 of academic year. The results of this research was to increase reading comprehension of English-language e-book was not too big. This is shown in the written test evaluation results in the second cycle, 5 students got a score of 82 and 5 students got a score of 28 students, and the average value is 66.25 Then, the SQ3R method can not only improve the ability to understand reading, but, the ability to read verbally where students have the opportunity to correct their reading. This is shown by the results of the second cycle evaluation, where 7 students got a score of 80, 6 students got score of 78 and 7 students got score of 75 of 28 students, and the average value was 72,60714286.